Development of SETS (Science, Environment, Technology, And Society) Oriented Chemical Learning Module on Natural Oil Concept - Ratna Sari Siti Aisyah; Indah Langitasari; Irma Sadiah (EduChemia (Jurnal Kimia dan Pendidikan), 2021)
The Indonesian government is trying to prepare the next generation of nations to deal with the globalization era; one of these is education. It was transformed in the application of Kurikulum 2013, in which the object of the learning process is more emphasis on phenomena or real events. But, the learning methods are still unvaried, and learning materials based on real-life problems are still not available, which creates a performance gap in the learning process. This research aims to cope with the performance gap by developing the saints, environment, technology, and society (SETS)-oriented module on petroleum topic and determine the students' response. The module developed in this research is done following a phase of the ADDIE developmental model. This developmental model consists of analyze, design, development, implementation, and evaluation. This SETS-oriented module has been trialed to 30 second-grade students of SMA Negeri 8 Kota Serang. According to validation and students' response, the SETS-oriented module developed is valid and got 87,37% of an average percentage of response, which includes great criteria